ZONASI TINGKAT KERENTANAN BANJIR DI KOTA BANJARBARU KALIMANTAN SELATAN - Enu Bahtiar Setiawan; Fadly Hairannoor Yusran; Fakhrur Razie; Rina Mustika (EnviroScienteae, 2015)
Zoning   Level  of Flood Susceptibility   in Banjarbaru City, South Kalimantan. This research aims to formulate  the control guide line  of flood susceptibility  in Banjarbaru, South Kalimantan   Province.  The goal is ac hieved through thest ages of study as follows:  1. Analyzing the characteristics  of Banjarbaru  City consisting of a) the use of land; b) rain fall; c) physical characteristics  of land (infiltration); and d) on steepness,  2.  Conducting  the zoning level of flood susceptibility  in Banjarbaru  City, and 3.Producing a chart of flood susceptibility for Banjarbaru  City. This research applies descriptive   method that consists of data gathering,  data processing  and data analysis. Determining  the high suspectibility  of flood  is done by weighting  indicators  of flood through  the closing   of land, the rain intensity,  the physical  characteristics   of  land (infiltration),  and the tilt of slope. uper weighting, classification  of flood  susceptibility  is carried out. Thecategory of level is done by multiplying  variable values with the variable weight.    Of fload  susceptibilityis divided  into four  categories: very fragile, ,fragile,  somewhat  fragile,  and not fragile. This research results flood  susceptibility  zoning level that aims to identify the areas that are fragile  to flood,  so this region can be analysed to prevent  and handle flood. Based on the result of data collection ,data processing  and data analysis, it can be  concluded   that:  1) based  on  the  results   of  the  analysis   toward   the flood susceptibility  variable,  it  can be concluded  that the cause of flood  susceptibility  in Banjarbaru  City is the change in the landuse because it has great weight beside the topography  of the area. Banjarbaru  City also has the tilt tendency  to beflat (0-8%), so the water from a higher place then will gather in this area. 2) Based on flood susceptibility  zoning level in Banjarbaru  City ,it is discovered  that an area of 16,810 hectares  or 51% of Banjarbaru  City's  width is located  in the level of somewhat fragile,  then an area of 13,118 hectares or 40% is not fragile  and 3,156 hectares or 9% is fragile to flood. 3) The chart of fload  susceptibility  in Banjarbaru  City has shown that almost all parts of areas in Banjarbaru  City are zones with high flood  susceptibility level with the criteria of not fragile ,somewhat fragile and fragile.